2017
DOI: 10.1038/s41598-017-13228-z
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale genomic analyses reveal the population structure and evolutionary trends of Streptococcus agalactiae strains in Brazilian fish farms

Abstract: Streptococcus agalactiae is a major pathogen and a hindrance on tilapia farming worldwide. The aims of this work were to analyze the genomic evolution of Brazilian strains of S. agalactiae and to establish spatial and temporal relations between strains isolated from different outbreaks of streptococcosis. A total of 39 strains were obtained from outbreaks and their whole genomes were sequenced and annotated for comparative analysis of multilocus sequence typing, genomic similarity and whole genome multilocus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Nevertheless, genes/proteins that play a key role in pathogenicity were detected with differential abundance among the temperatures. Although the fish-adapted GBS strains had evolved in divergent branch from mammalian GBS isolates (Barony et al, 2017 ), several genes are shared among piscine and mammalian strains (Rosinski-Chupin et al, 2013 ; Kawasaki et al, 2018 ), including those identified as differentially expressed in our study. Therefore, upregulation at 32°C of proteins IagA, CpsB and cAMP factor may be important for the onset of streptococosis in tilapia during the warmer months.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Nevertheless, genes/proteins that play a key role in pathogenicity were detected with differential abundance among the temperatures. Although the fish-adapted GBS strains had evolved in divergent branch from mammalian GBS isolates (Barony et al, 2017 ), several genes are shared among piscine and mammalian strains (Rosinski-Chupin et al, 2013 ; Kawasaki et al, 2018 ), including those identified as differentially expressed in our study. Therefore, upregulation at 32°C of proteins IagA, CpsB and cAMP factor may be important for the onset of streptococosis in tilapia during the warmer months.…”
Section: Discussionmentioning
confidence: 64%
“…The isolate selected for these analyses was the GBS SA53 strain. This strain was previously isolated from diseased Nile tilapia in Brazil (Mian et al, 2009 ) and belongs to ST-260, one of the most frequently identified genotypes in Latin America (Evans et al, 2008 ; Delannoy et al, 2013 ; Godoy et al, 2013 ; Barato et al, 2015 ; Barony et al, 2017 ). SA53 belongs to a group of fish-adapted genotypes that descend from a single branch unlike human GBS strains, and are going through reductive genome evolution (Barony et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, capsular serotypes Ⅲ, Ia, Ib and Ⅴ are the most common in humans in China (Jiang et al, ; Wang et al, ). However, in the past decade, GBS strains of the Ia, Ib and III serotypes were shown to predominate in fish infections, and serotype Ia and Ib strains are mainly responsible for tilapia streptococcosis (Barato, Martins, Melo‐Cristino, Iregui, & Ramirez, ; Barony et al, ; Li et al, ). In China, an epidemiological study showed that the serotype Ia GBS strain is the most frequent serotype in tilapia infection, accounting for >90% of all GBS isolates (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%